1991
DOI: 10.1203/00006450-199102000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of Biologically Active and Immunoreactive Intact Parathyroid Hormone in Human Newborns

Abstract: ABSTRACT. We evaluated circulating levels of biologically active and immunoreactive intact parathyroid hormone in 47 newborns at birth and eight hypocalcemic preterm infants during the first 10 d of life. Use of two sensitive detection systems, the cytochemical bioassay and an immunoradiometric assay specific for intact parathyroid hormone, enabled us to compare plasma concentrations of PTH-like bioactivity (bioPTH) and iPTH-(1-84). Mean umbilical venous plasma bioPTH was elevated in nondiabetic term and pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 46 publications
4
17
0
Order By: Relevance
“…The data demonstrate that in combination, low concentrations of either fragment could abolish the effects of 10 nM PTH-(1-34) on calcium release and repression of ALP activity. This finding that different parts of the PTH molecule can exert opposing effects at widely differing concentrations suggests that distinct PTH-domains exert agonist and antagonist actions on bone tissue and are consistent with other findings, where low concentrations of PTH showed growth enhancing activities in avian [15,16] and in other cellular systems [17,18]. For determine a dose related response for both fragments a higher dilution may be required.…”
Section: Discussionsupporting
confidence: 88%
“…The data demonstrate that in combination, low concentrations of either fragment could abolish the effects of 10 nM PTH-(1-34) on calcium release and repression of ALP activity. This finding that different parts of the PTH molecule can exert opposing effects at widely differing concentrations suggests that distinct PTH-domains exert agonist and antagonist actions on bone tissue and are consistent with other findings, where low concentrations of PTH showed growth enhancing activities in avian [15,16] and in other cellular systems [17,18]. For determine a dose related response for both fragments a higher dilution may be required.…”
Section: Discussionsupporting
confidence: 88%
“…In the decades that followed the development of specific PTH assays, it was recognized that fetal blood contains high PTH-like bioactivity but low immunoreactive levels of PTH (3,20,21,67,571). PTHrP was cloned in 1987 (410,646,658), and subsequent work confirmed that it mimics many of the biological actions of PTH (333), circulates at high levels in fetal blood compared with PTH (168,306,600,671), and accounts for the high PTH-like bioactivity in fetal blood (7,94,396).…”
Section: Parathyroid Hormone-related Proteinmentioning
confidence: 99%
“…B) HUMAN DATA. As with animal fetuses, prior to the discovery of PTHrP it was recognized that human cord blood contained low immunoreactive intact PTH concentrations but high levels of PTH-like bioactivity as measured in cytochemical bioassays (20,21,571). The discrepancy is now explained by high circulating levels of PTHrP (600, 671), which mimics many of the actions of PTH on the PTH1R.…”
Section: Pthrpmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although 1,25-D (given at pharmacologic doses to the dam or fetus) can increase the fetal calcium content and blood level of calcium (7,8), fetuses of severely vitamin D-deficient, hypocalcemic rats have normal blood calcium levels and fully mineralized skeletons (9,10). Maternally derived PTH cannot cross the placenta (11), and fetal immunoreactive PTH levels are low throughout gestation in mammals (3,12).…”
mentioning
confidence: 99%